Interface : prize-winning, sustainable modular flooring - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
Interface, Inc., winner of the inaugural Sustainability Survey, is a global corporation which markets modular carpet. This case study examines Interface's commitment to sustainability through its marketing strategy. Readers are asked to evaluate Interface's current position as a leader in sustainable practice and how the corporation can ensure continued success in this area.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Interface: Prize-Winning, Sustainable Modular Flooring. In International marketing (pp. 260-261). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Interface, Inc; Sustainable development -- Case studies; Marketing -- Case studies